The Third International Conference on the Development of Biomedical Engineering in Vietnam BME2010January 11 - 14th, 2010Ho Chi Minh City, VIETNAM - Van Toi, Vo; Khoa, Truong Quang Dang (IFMBE Proceedings,, 2010)
The Third International Conference on the Development of Biomedical Engineering in Vietnam was organized on January 11-14, 2010, by IU in Ho Chi Minh City, Vietnam and had the theme of: "New frontiers in Biomedical Engineering". It reflected the steady growth of the activities in this field in Vietnam, and featured the contributions of researchers of 21 countries, including: Australia, Belgium, Canada, Denmark, France, India, Japan, Korea, Malaysia, New Zealand, Philippines, Poland, Russia, Singapore, Spain, Switzerland, Taiwan, Thailand, United Kingdom, the United States and Vietnam. Besides the invited, oral and poster presentations there were tutorial lectures to educate junior researchers in different subfields of Biomedical Engineering. This volume summarizes those presentations and was provided as an education foundation and scientific reference.